2020
DOI: 10.1177/0020764020943230
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness within the general population of Slovenia

Abstract: Background: While loneliness is recognized as a risk to mental and physical health, there is a lack of data covering a broad age range. This study used a Slovenian adult sample to investigate loneliness. Aims: To examine levels of social, emotional and general loneliness within the general population. Method: A survey on a sample representative of the general population ( N = 1,189; aged between 18 and 95 years old ( M = 46.74, standard deviation ( SD) = 16.18); 49.7% were men) was conducted in Slovenia by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…B = −1.36, SE = 0.13, β = −0.11, t = −10.61*, Part r = −0.10. Lavric et al (2020) General: 2.68**(SD = 1.77). Emotional: 0.80**(SD = 1.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…B = −1.36, SE = 0.13, β = −0.11, t = −10.61*, Part r = −0.10. Lavric et al (2020) General: 2.68**(SD = 1.77). Emotional: 0.80**(SD = 1.01).…”
Section: Resultsmentioning
confidence: 99%
“… Response categories: employed; not employed. C Univariate analysis, multiple regression – ordinary least squares, binary logistic and ordered logistic regression (descriptive statistics – percentage, ordered logistic regression) b Lavric et al (2020) Examine levels of social, emotional and general loneliness in the general population 1189 Range: 18-95 Mean: 46.74 SD: 16.18 49.7% male Slovenia Mental Health Literacy Project, 2018–2020 Cross-sectional De Jong Gierveld short scales D Survey data. Response categories: student; employed; unemployed; retired; retired due to disability.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previous study, we found that being single, divorced, or widowed; living alone; and having cardiocerebrovascular diseases were associated with loneliness ( 5 , 28 , 31 ). However, previous findings on the association between age and loneliness have been inconsistent across studies ( 3 , 32 , 33 ). Consistent with two previous studies ( 3 , 32 ), we found that age was negatively correlated with loneliness.…”
Section: Discussionmentioning
confidence: 90%
“…In Slovenia, loneliness appears to be related to poor interpersonal relationships, which is also suggested by the fact that the lowest level of loneliness there seems to be among the married population (Lavrič et al. 2021 ). Yet we disregard an aggregation of this explanation, since the country has comparatively low marriage rates (Eurostat 2021 e).…”
Section: Discussionmentioning
confidence: 94%